Maridos furiosos, frustrados y débiles. Fisuras del régimen patriarcal y relaciones de poder intergéneros en procesos de divorcio perpetuo. Desde la República de Rosas a la Argentina liberal - Ghirardi, Mónica (El Colegio de México, A.C., 2025)
The exercise of male authority in marriage and the family required the recognition of the members of a household. Full obedience and compliance with the will of the husband and father depended on multiple factors and did not always occur. This point constitutes one of the keys to understanding cross-gender relations within marriage, the family and society. This article analyzes the way in which social supremacy,one’s network of relationships within the community, the prestige of one’s family name, ties to the political and religious powers that be, a household’s economic situation, one’s age, previous marriages, the sociopolitical juncture and one’s lifestyle could either strengthen or undermine the exercise of male power on a practical level in domestic and family life in late-nineteenth-century Córdoba. The judicial records used as a primary source constitute exceptional records of mechanisms of power and an arena for conflicting representations,cultural practices and judicial policies.